Pheromone communication in moths evolution, behavior, and application - Allison, Jeremy D., 1973-; Cardé, Ring T. (University of California Press, 2016)
"Common among moths is a mate-finding system in which females emit a pheromone, which induces males to fly upwind along the pheromone plume. Following the chemical identification of the pheromone of the domesticated silk moth in 1959, the number of moth species with identified pheromone attractants has climbed steadily, providing a rich base for review and synthesis. Pheromone Communication in Moths summarizes moth pheromone biology, including the chemical structures used by the various lineages, signal production and perception, the genetic control of moth pheromone traits, interactions of pheromones with host plant volatiles, pheromone dispersal and orientation, male pheromones and courtship, and the evolutionary forces that have likely shaped these pheromone signals and their role in sexual selection. Also included are chapters on practical applications in the control and monitoring of pest species as well as case studies of pheromone systems of a number of species and groups of closely allied species. Pheromone Communication in Moths will be an invaluable resource for entomologists, chemical ecologists, and pest management scientists, as well as for those studying pheromone communication and pest management"--Provided by publisher.